Maternal Spirulina supplementation during pregnancy and lactation partially prevents oxidative stress, glial activation and neuronal damage in protein malnourished F1 progeny. (December 2020) - Sinha, Shrstha; Patro, Nisha; Tiwari, P.K.; Patro, Ishan K.
Abstract: Protein malnutrition (PMN) is a global health issue but most prevalent in Africa and Asia. It exerts detrimental effect on structural and physiological aspects of hippocampal circuitry. Despite accumulating evidence for PMN induced changes in nervous system, relatively very little is known about how maternal nutritional supplementation during malnutrition affects glial cells and neurons. Herein, we aimed to investigate the effects of maternal Spirulina supplementation against PMN induced oxidative stress, reactive gliosis and neuronal damage in hippocampus of F1 progeny. Three months old healthy Sprague Dawley females (n = 24) were shifted to normoprotein (NC; 20% protein) and low protein (LP; 8% protein) diets 15 days before conception. The NC and LP group females were subdivided into two groups according to Spirulina supplementation (400 mg/kg/b.wt. orally throughout gestation and lactation period): normal control with Spirulina (NC SPI) and low protein with Spirulina supplemented group (LP SPI). F1 progeny born were used in present study. Thus, building on earlier results of ameliorated neurobehavioral and cognitive abilities in Spirulina supplemented protein deprived rats, the present study incorporates neurochemical and morphometric analysis of glial cells and neurons and revealed that maternal Spirulina consumption partially prevented the PMN associated neuropathological alterations in terms of attenuated oxidative brain damage, reduced reactive gliosis and apoptotic cell population, improved dendritic branch complexity with few damaged neurons and enhanced mushroom shaped spine density. The results suggest that cellular changes in hippocampus after PMN are partially restored after maternal Spirulina supplementation and one could envision intervention approaches using Spirulina against malnutrition.